The influence of AI-enabled tool adoption, digital footprints, and SME credibility on loan approvals: a quantitative study of South African SMEs - Ntshakala, Thembekile (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.